Jogo Didático com Intuito de Ajudar na Alfabetização de Crianças com Dislexia - Silva, Danna Thayne Gomes da (Brasil, 2022)
The present project proposes the creation of a board game that helps in the literacy of children with dyslexia. The work was carried out based on bibliographic research that focused on searching for methodologies that are used to help dyslexic children during this period. Research was carried out on the influence of game design, on the experiences of teachers in the public school system and their understanding of dyslexia. And also about how dyslexic children feel when they are not optimally included in schools. Game design has contributed to several areas of education, especially the branch of children's literature that helps children's cognitive development. It was observed that the parents' lack of knowledge and experience of some teachers in the primary education network generates frustration in children who suffer from some learning disorder. To improve their experience in schools, several games are created to meet this need during the literacy phase, making education more inclusive, since they are classified as didactic tools. In conclusion, the project met the previously imposed needs, but to achieve better results, there is a recommendation to carry out tests to have a better application.